Transnational Democracy in Ecuador: the Impact of Voting Abroad and Migrant Representation (Andamios, Revista de Investigación Social, 2026)
On the global stage, Ecuador stands out as one of the few countries that grants its citizens abroad the right to vote and the ability to elect migrant representatives to the legislature. This expansion of political-electoral rights has the potential to profoundly influence multiple dimensions of Ecuadorian democracy. In this article, we examine this issue through an analysis grounded in empirical evidence, exploring the effects of external voting and the allocation of legislative seats in relation to democratic quality, political representation, and technological advancements. Based on this, we argue that these mechanisms contribute to the inclusion of historically marginalized sectors, the strengthening of political culture, and the broadening of the concept of citizenship.
Keywords: Ecuador; democracy; technology; migration; social exclusion